Demonstration of direct ocean carbon capture using hollow fiber membrane contactors - Joanna Rivero; Austin Lieber; Christopher Snodgrass; Zöe Neal; Marina Hildebrandt; William Gamble; Katherine Hornbostel (Chemical Engineering Journal, 2023)

Leatherback Turtles in the Eastern Gulf of Mexico: Foraging and Migration Behavior During the Autumn and Winter - Christopher R. Sasso; Paul M. Richards; Scott R. Benson; Michael Judge; Nathan F. Putman; Derke Snodgrass; Brian A. Stacy (Frontiers in Marine Science, 2021)
We deployed 19 satellite tags on foraging adult leatherback turtles, including 17 females and 2 males, captured in the northeastern Gulf of Mexico in 2015, 2018, and 2019 in order to study regional distribution and movements. Prior to our study, limited data were available from leatherbacks foraging in the Gulf of Mexico. Tag deployment durations ranged from 63 to 247 days and turtles exhibited three distinct behavior types: foraging, transiting, or rapidly switching between foraging and transiting. Some females were tracked to nesting beaches in the Caribbean. Most of the leatherbacks remained on and foraged along the west Florida continental shelf whereas a few individuals foraged in waters of the central Gulf of Mexico during the autumn and winter. In addition, migration of adult females through the Yucatan Channel indicate that this is a seasonally important area for Caribbean nesting assemblages.

Habitat Use and Behavior of Multiple Species of Marine Turtles at a Foraging Area in the Northeastern Gulf of Mexico - Natalie E. Wildermann; Christopher R. Sasso; Lesley W. Stokes; Derke Snodgrass; Mariana M. P. B. Fuentes (Frontiers in Marine Science, 2019)

Salinization alters ecosystem structure in urban stormwater detention ponds - Robin J. Van Meter; Christopher M. Swan; Joel W. Snodgrass (Urban Ecosystems, 2011)

Road Salt Stress Induces Novel Food Web Structure and Interactions - Robin J. Van Meter; Christopher M. Swan; Jeff Leips; Joel W. Snodgrass (Wetlands, 2011)